Comparative study of the antiproliferative activity of heterometallic carbene gold(I)-platinum(II) and gold(I)-palladium(II) complexes in cancer cell lines - Dietl, Martin C.; Maag, Melina; Ber, Sophia; Rominger, Frank; Rudolph, Matthias; Caligiuri, Isabella; Andele, Pacome K.; Mkhalid, Ibraheem A. I.; Rizzolio, Flavio; Nogara, Pablo A.; Orian, Laura; Scattolin, Thomas; et al. (Chemical science, 2024)
The stepwise, one-pot synthesis of heterobimetallic carbene gold(I) platinum(II) complexes from readily available starting materials is presented. The protecting group free methodology is based on the graduated nucleophilicities of aliphatic and aromatic amines as linkers between both metal centers. This enables the selective, sequential installation of the metal fragments. In addition, the obtained complexes were tested as potential anticancer agents and directly compared to their gold(I) palladium(II) counterparts.
Gesehen am 14.10.2024